The Fallacy of the Fiscal Theory of the Price Level, Again - Willem Buiter (Center for Economic Studies and ifo Institute (CESifo), 2000)
The Fiscal Theory of the Price Level (FTPL) rejects the fundamental 'Ricardian' proposition, that the government budget constraint must hold identically, that is for all admissible values of the variables entering the budget constraint. Accordingly, if the government is to meet its contractual debt obligations, one of its instruments must be determined residually to ensure the budget constraint is satisfied. If the government overdetermines its fiscal-financial-monetary policy programme, contractual debt obligations will not be met. The FTPL asserts that even when the government overdetermines its policy programme, contractual debt obligations will always be met. The general price level plays the role of a default premium or discount. The paper shows that the FTPL is a fallacy and leads to anomalies and contradictions.
Keywords: 330; Fiscal theory of the price level; Ricardian fiscal rules; government budget constraint; price level indeterminacy